Jodipan sebagai Implementasi Desa Wisata Madani - Harun Al Rasyid; Ahsani Taqwiem (Program Studi Ekonomi Syariah Institut Agama Islam Sunan Kalijogo Malang, 2019)
Nowadays, halal tourism with economic community empowerment being goverment concentration in advancing the economy in Indonesia. Asset based community development is one of the method approach on empowering the economic community. Then, village assets such as nature, humans, and other resources become a potential empowerment and welfare of the village community. Jodipan as one of the tourism village destination has the both element : residents and village officials participated in the development and empowerment of the village community, is in line with Islamic principles, namely maqashid Syari’ah. This study exerts a qualitative approach with case study on Jodipan tourism village. Data from this study were obtained by conducting observations, interviews, and documentation. While the data were analyzed by triangulation method to determine the validity of the data obtained. Through this research, it was found that halal tourism development in Jodipan village has a great strategy to build the village, as like the role of government of keeping al-Dharuriyat, industry sector which can be material, financial, or empowerment training and private industry as for keeping al-Hajjiyat, and maintaining tahsiniyat by using mass media to support promotional activities.